The Values of Recommendations by Quality Assurance Papers: The Case of Vietnam (Journal of Contemporary Educational Policies and Practices, 2023)
Many scientific articles on quality in higher education are published every year. Ideally, these articles are read, studied and moreover used by others. However, the usability of articles on quality in higher education by scholars and quality responsible staff in institutions is not obvious. Do the right people read the articles? And moreover, are the recommendations of these articles transportable to the different contexts they are working in? This article summarizes some of the lessons learned from the articles published in the journal Quality in Higher Education from September 2021 to October 2022. It also relates the results to the Vietnamese higher education context. In doing so, the article presents a set of useful findings of international research for higher education in Vietnam and maybe in other Asian countries in comparable contexts. Furthermore, the authors propose a way to determine the usability of research results in another context.
Keywords: Internal quality assurance; quality management; context analysis; rapid review; research applications